Extremism in Muslim feminism and the balanced scale - Isahak, Aldila (2014)
Feminism seeks to remedy the injustice and inequalities confronting women and society at large. Within this broad social movement, points of tension exist between different camps whose trends of thought differ from one another even though they head in one direction. In staying clear of extremisms that could tilt the scale of social justice in Islam, this talk discusses the significant of adopting the equilibrium that ensures the scales are not tilted at either end. By exploring Muslim feminist liberal thought and the patriarchal saturated cultural practices of the Muslims, the concept of ummatan wasatan of Islamic feminism is expounded.